Effects of Melatonin on Memory and Learning Deficits Induced by Exposure to Thinner - Nedzvetskii, V. S.; Kirichenko, S. V.; Baydas, G.; Nerush, O. P. (Springer, 2012)
The neurotoxic effects of thinner, a mixture including aromatic compounds (in particular, toluene) and widely used as an industrial solvent, were examined. Exposure of rats to high inhalation concentrations (3000 p. p. m.) of thinner for 45 days (1 h per day) significantly influenced the cognitive functions and levels of neural cell adhesion molecules (NCAM) in the hippocampus, cortex, and cerebellum of experimental animals. These exposures also caused dramatic increases in levels of LPO (malondialdehyde and 4-hydroxyalkenals) in these cerebral structures, while melatonin administration significantly reduced the LPO amounts in these brain regions. The level of NCAM (180 kDa) decreased significantly in the hippocampus and cortex of thinner-exposed rats. Furthermore, thinner-exposed rats showed cognitive deficits in the passive avoidance and Morris water maze tasks; these negative effects were considerably compensated in rats additionally chronically treated with melatonin. It is concluded that treatment with melatonin prevents the development of learning and memory deficits caused by thinner exposure, possibly by reducing oxidative stress and normalizing the neural plasticity.
Keywords: learning; lipid peroxidation; melatonin; neural cell adhesion molecules; thinner